Neotectonics induced by ice-sheet advances in NE Poland - Morawski, Wojciech (Bogucki Wydawnictwo Naukowe, 2009)
Differences in the geological structure of the hard-rock substratum of the Warmia and Mazury regions (NE Poland) resulted during the Pleistocene in different reactions on the load exerted by the land-ice masses. In the (western) Warmia province, vertical glacio-isostatic movements caused cyclic erosional events affecting the relatively thick sedimentary cover, which became more compacted. In contrast, the thinner sedimentary cover of the rigid crystalline basement favoured quiet sedimentation in the (eastern) Mazury province. The zone in between these two areas runs NNE-SSW for some 80 km. It is several kilometres wide and is composed of landforms that owe their origin to the sedimentary infilling of crevasses. This intermediate zone formed an interlobe are between the two huge ice lobes that covered the Warmia and Mazury areas during the last ice age. The basement of the zone coincides with the crystalline craton slope, which is accompanied to the west by a parallel marginal trough. Cyclic advances and retreats of the Pleistocene ice sheet induced neotectonic mobility. Glacio-isostatic processes resulted in the intermediate zone in block movements (uplift and subsidence) that affected the whole Cenozoic succession, creating mainly vertical discontinuity zones. Glacio-isostasy also induced vertical tectonic movements within the older deposits, reaching down to the crystalline basement. A tectonic graben thus developed. It is bounded by flexures accompanied on both sides by positive structures that may indicate transpressional movements with a strike-slip stress component.
Keywords: Neotectonics; Glacioisostasy; Glaciotectonics; Geophysical investigations; Pleistocene; NE Poland